Epidemiology of rugby-related fractures in high school- and college-aged players in the United States: an analysis of the 1999-2018 NEISS database - Etzel, C. M.; Wang, K. H.; Li, L. T.; Nadeem, M.; Owens, B. D. (The Physician and Sportsmedicine, 2022)
Objectives Rugby is a high-impact collision sport with identical competition rules by sex. The aim of this study was to analyze the trend of rugby-related fractures by body site, sex, and age in amateur athletes from 1999 to 2018.